2023
DOI: 10.1128/spectrum.03539-22
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Lysine Acetylation Reveals Diverse Functions in Azorhizobium caulinodans Strain ORS571

Abstract: Acetylation is an important modification that regulates protein function and has been found to regulate physiological processes in various bacteria. The physiology of rhizobium A. caulinodans ORS571 is regulated by multiple mechanisms both when free living and in symbiosis with the host; however, the regulatory role of acetylation is not yet known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…59 Azorhizobium caulinodans contains 2302 acetylation sites on 982 proteins, and as with many bacterial species, acetylated proteins were involved in energy metabolism. 60 In particular, acetylated proteins were enriched in the TCA cycle, ribosomes, metabolism of glycerol and lipids, glucose, pyruvate metabolism, and bacterial chemotaxis. One acetylated protein, the chemotaxis master regulator CheY, was further examined.…”
Section: Understanding Of Lysine Acylations In Bacteriamentioning
confidence: 99%
“…59 Azorhizobium caulinodans contains 2302 acetylation sites on 982 proteins, and as with many bacterial species, acetylated proteins were involved in energy metabolism. 60 In particular, acetylated proteins were enriched in the TCA cycle, ribosomes, metabolism of glycerol and lipids, glucose, pyruvate metabolism, and bacterial chemotaxis. One acetylated protein, the chemotaxis master regulator CheY, was further examined.…”
Section: Understanding Of Lysine Acylations In Bacteriamentioning
confidence: 99%
“…Mass spectrometry analysis of different bacterial proteomes has identified many acetylation sites on proteins. The functional annotation showed that some of the acetylated proteins are involved in translation and transcription ( Weinert et al., 2013 ; Nakayasu et al., 2017 ; Christensen et al., 2019b ; Marakasova et al., 2020 ; Liu et al., 2023 ).…”
Section: Lysine Acetylation Is Involved In Bacterial Translationmentioning
confidence: 99%